Antibacterial Properties of Organosulfur Compounds of Garlic (Allium sativum) - Bhatwalkar, Sushma Bagde; Mondal, Rajesh; Krishna, Suresh Babu Naidu; Adam, Jamila Khatoon; Govender, Patrick; Anupam, Rajaneesh (Frontiers in Microbiology, 2021)
Garlic (Allium sativum), a popular food spice and flavoring agent, has also been used traditionally to treat various ailments especially bacterial infections for centuries in various cultures around the world. The principal phytochemicals that exhibit antibacterial activity are oil-soluble organosulfur compounds that include allicin, ajoenes, and allyl sulfides. The organosulfur compounds of garlic exhibit a range of antibacterial properties such as bactericidal, antibiofilm, antitoxin, and anti-quorum sensing activity against a wide range of bacteria including multi-drug resistant (MDR) strains. The reactive organosulfur compounds form disulfide bonds with free sulfhydryl groups of enzymes and compromise the integrity of the bacterial membrane. The World Health Organization (WHO) has recognized the development of antibiotic resistance as a global health concern and emphasizes antibiotic stewardship along with the urgent need to develop novel antibiotics. Multiple antibacterial effects of organosulfur compounds provide an excellent framework to develop them into novel antibiotics. The review provides a focused and comprehensive portrait of the status of garlic and its compounds as antibacterial agents. In addition, the emerging role of new technologies to harness the potential of garlic as a novel antibacterial agent is discussed.